Borrelia burgdorferi sensu lato in Ixodes cf. neuquenensis and Ixodes sigelos ticks from the Patagonian region Argentina - Saracho Bottero, María Noelia; Lareschi, Marcela; Venzal, José Manuel; Carvalho, Luis A.; Nava, Santiago; Sebastian, Patrick Stephan; Mackenstedt, Ute (2017)
This study was conducted to detect Borrelia burgdorferi sensu lato infection in ixodid ticks from the Patagonia region in the south of Argentina. Therefore, ticks were collected on rodents in the provinces of Chubut, Río Negro and Santa Cruz. These ticks were identified as nymphs of Ixodes cf. neuquenensis and Ixodes sigelos. The B. burgdorferi s.l. infection was tested by a battery of PCR methods targeting the gene flagellin (fla) and the rrfA-rrlB intergenic spacer region (IGS). Three pools of I. sigelos nymphs from Chubut and Santa Cruz provinces as well as one pool of I. cf. neuquenensis nymphs from Río Negro province were tested positive in the fla-PCR. The samples of I. sigelos were also positive for the IGS-PCR. Phylogenetically, the haplotypes found in the positive ticks belong to the B. burgdorferi s.l. complex, and they were closely related to Borrelia chilensis, a genospecies isolated from Ixodes stilesi in Chile. The pathogenic relevance of the Borrelia genospecies detected in both I. neuquenensis and I. sigelos is unknown